Evaluating Geodesign for Community-Based Tribal Planning: The Role of Planners in Marginalized Communities. Issue 4 (2nd October 2021) - Davis, Jonathan; Pijawka, K. David; Wentz, Elizabeth; Hale, Michelle; King, David A.
Abstract: Problem, research strategy, and findings: Geodesign is a technology-supported planning approach that combines community collaboration and engagement with geospatial analysis to make land use decisions quickly. In this study we tested the role of Geodesign in improving the quality of local plans through community participation and collaborative decision making supported by geospatial analysis. Our research evaluates Geodesign as a tool and process in establishing community engagement in planning decisions by applying and analyzing Geodesign in two Navajo Nation communities in Arizona to use scientific and community knowledge to make consensus-based decisions for land use planning. There are three critical components to this analysis. First, we evaluate the use of Geodesign as a plan-making tool. Second, we examine how Geodesign can be inclusionary for planning using Arnstein's ladder of citizen participation with marginalized American Indian communities. Finally, we look at the planner's role and required planning expertise in developing successful Geodesign plans. We conclude that Geodesign can empower historically marginalized Indigenous communities to make community-based land use plans that leverage local knowledge/values and geospatial analysis. Takeaway for practice: Planners can use Geodesign approaches to collaborate and guide marginalized communities to engage in the planning process and incorporate diverse perspectives and cultural values in decision making. A planner should judiciously apply their expertise in their role as a planning facilitator, trainer, and knowledge resource. Using geospatial data and community engagement, Geodesign produces community-based land use plans.